Political Realism in the Chinese Warring States Period and the European Renaissance:: Han Fei and Machiavelli - Kallinikos, Panagiotis (Conatus - Journal of Philosophy, 2023)
Τhis article presents the basic similarities and differences between the Political Realism of Niccolò Machiavelli in the 15th century A.D., i.e. during the Renaissance in Europe, and the Chinese Legalism of Han Fei in the 3rd century B.C., during the Warring States period. It could be supported that Political Realism and Political Legalism share numerous elements that bring them closer rather than apart. The fundamental works written by the main representatives of these two political doctrines, namely the Prince by Machiavelli and the Han Feizi by Han Fei, are addressed to living political leaders, specifically Lorenzo de' Medici and the governor of the Hann state in the Warring States historical period (476-221 B.C.) respectively. Both philosophical movements emphasize the importance of statesmanship in a ruler and reject the idealistic approach to politics. Machiavelli and Han Fei do not promote a cruel leadership, but straightforwardly condemn morality alone as insufficient for the establishment of a state. Both of them try to replace previous models of virtuous political philosophy – that of classical antiquity in the case of Machiavelli and that of Confucianism in the case of Han Fei – with a new notion of political correctness which takes into account the urgency of the moment and ensures political stability.